Spatio-temporal development of CYP1 activity in early life-stages of zebrafish (Danio rerio) - Otte, Jens Christopher; Schmidt, Annette D.; Braunbeck, Thomas (Aquatic toxicology, 2010)
Endpoints of planar halogenated aromatic hydrocarbon (pHAH) and polycyclic aromatic hydrocarbon (PAH) toxicity are mediated via activation of the aryl hydrocarbon receptor (AhR) followed by activation of the so called “AhR-battery” of genes including the cytochrome P450 1 (CYP1) isoforms. The aim of this study was to develop a method to identify CYP1 activity in early life-stages of zebrafish (Danio rerio) in order to elucidate the spatio-temporal pattern of basal and induced CYP1 activities. Preliminary experiments with the fish embryo toxicity test (FET) were carried out to determine toxic effect thresholds of the AhR agonist β-naphthoflavone. To assess basal and β-naphthoflavone-induced CYP1 activity during early life-stages of zebrafish, the commonly used 7-ethoxyresorufin-O-deethylase (EROD) assay was developed further for use in confocal laser scanning microscopy (CLSM) and spectrometry. Following exposure to selected cytochrome P450 inducers, zebrafish embryos were dechorionated, anaesthetized and inspected in vivo under the CLSM. Alternatively, embryos were homogenized, and EROD activity was measured using classical spectrometry in vitro. CLSM of CYP-induced fluorescence allowed for the in vivo detection of CYP1 enzyme activity down to the cellular level as early as in the gastrulation stage. Basal and induced CYP1 activity was detected at all time points examined from 8 h post-fertilization to early adulthood and showed a highly dynamic spatio-temporal pattern throughout zebrafish development. Basal and induced EROD activity was prominent in tissues of the cardiovascular system, the urinary tract, the digestive system, and parts of the brain as well as in the central portion of the eye and the otic vesicle during distinct stages of development. The differentiation between constitutive and induced spatio-temporal patterns of CYP1 activity even as early as the gastrula stage provide further insights into the endogenous role of CYP1 activity.